DEVELOPING 3-D SNAKE AND LADDER GAME: THE IMPLEMENTATION AT THE SECOND GRADE STUDENTS OF SDN 37 PEKANBARU - Dian Febriyanti; Zetra Hainul Putra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to test the feasibility of a 3D snake and ladde game to reflect the thematic learning materials from theme 6 subthemes 2 about “Taking Care of Animals around Me”. This study was conducted in June 2020 in one of the parents’ house of the second grade students of SDN 37 Pekanbaru. This research was motivated by the lack of learning media for primary school students. The learning outside the learning hours was important for students to have additional learning activities, working together in groups, respecting friends' opinions, and interacting. The 3D snake and ladder game was an interesting game. The development of 3D snake and ladder game was conducted according to the Research and Development (R&D) method with the procedure of ADDIE development models. The feasibility test of 3D snake and ladder game found that the prduct was valid with the validation rate of 87.5% from the media expert (very acceptable category) and 92.5% from the content expert (very acceptable category). Moreover, the percentage of students’ responses to the snake and ladder game was 95.97% (excellent category).